An Assessment of the Effect of Fiscal Decentralisation on Performance of County Governments in Kenya - Mbau, Elias Peter; Iraya, Cyrus; Mwangi, Mirie; Njihia, James (European Scientific Journal, ESJ, 2019)
The paper focused on the analysis of the influence of fiscal decentralization (FD) on the performance of County governments in Kenya during the transitionary period from a central to a decentralised governance system (2013-2018). The quest for fiscal decentralisation has taken center stage in the past three decades in many parts of the word including Latin America, Asian countries, Africa and throughout the formally planned economies. The study was prompted by conflicting findings from previous empirical studies in both developed and the developing countries. Three indicators of fiscal decentralisation were defined and used in the study. These are the ratio of county governments’ funds received from the National Government and local revenue collections. The other is transfer grants, defined as both conditional and unconditional funds received from both national government and development partners. Multiple regression analysis and correlation analysis were used to estimate the parameters of the model. The study was descriptive and used panel data to offer a comprehensive profile of the key variables identified in the conceptual framework. The unit of analysis was the County government with all the 47 counties forming the population of study. The results reveal that 27.43% of variations in the performance of County Governments are explained by the variables in the model and that equitable share (UB) has the most significant influence. From the several tests applied, the prediction model was confirmed as appropriate.